Pengaruh Motivasi Kerja, Stres Kerja dan Kepuasan Kerja terhadap Komitmen Organisasi Guru SD Program Sekolah Penggerak di Kabupaten Aceh Utara - Lili Andasna; Silvi Listia Dewi; Hera Yanti (Departement of Mathematics Education, 2024)
The purpose of this study is to determine the effect of work motivation on organizational commitment, the effect of job stress on organizational commitment, and the effect of job satisfaction on organizational commitment, as well as the combined effect of work motivation, job stress, and job satisfaction on the organizational commitment of elementary school teachers in the “School Movement” program in North Aceh Regency. This study was conducted at elementary schools in the “School Movement” program in North Aceh Regency. The study population totaled 380 people, with a sample of 76 individuals determined proportionally according to their work units. The instrument used was a questionnaire. Data analysis for this study employed the Product Moment correlation and Multiple Regression techniques. The results of the study indicated that (1) work motivation has a positive effect on organizational commitment by 58.1%. (2) Job stress has a negative effect on organizational commitment, with a correlation value of 0.027 and a total effect of 0.1%. (3) Job satisfaction has a positive effect on organizational commitment, with a correlation value of 0.057 and a total effect of 39%. (4) Collectively, work motivation, job stress, and job satisfaction affect organizational commitment with a significance value of 0.007 at a 0.05 significance level. The results of this study demonstrate that work motivation, job stress, and job satisfaction can influence organizational commitment. Therefore, to enhance organizational commitment, it is necessary to improve work motivation, reduce job stress, and increase job satisfaction among teachers.